Materiais funcionais baseados em sistemas poliaromáticos: fenacenos-tetracarboxilatos e -tetracarboxidiimidas, e azobenzenos-tetracarboxilatos - Moreira, Thamires dos Santos (2019)
Searches on the development of new materials for specific applications has become a great challenge in scientific community, in order to achieve the global technological demands. In this direction, efforts were made to introduce materials with functionalities based on a combination of multiple components. This work presents the synthesis and characterization of the optoelectronic properties of tetracarboxy-functionalized phenacenes and azobenzenes. [8], [10], [12] and [14] phenacenetetracarboxylates were obtained by double Perkin condensations, followed by oxidative photocyclization; whereas, the [8], [10], [12] and [14] phenacenestetracarboxdiimides were synthesized from the respective phenacenestetracarboxylates with an appropriate symmetric (dialkylmethyl)amine. Optical and electrochemical properties were studied, with the diimides exhibiting significantly lower band gaps than the esters. [12] phenacenetetracarboxylate compound exhibited liquid crystalline property, with a monotropic nematic phase at 210 °C. Azobenzenetetracarboxylates were obtained by Fischer esterification with the respective linear and branched alcohols. These compounds showed a good thermal stability, with decomposition temperatures above 300 °C, and two of them are liquids at room temperature (octyl and 2-ethyl-hexyl isomers). A decrease in the melting point of these compounds was observed as the linear chains were increased (Me > Et > Pr > Bu > Pent > Hx > Oct). All azocompounds exhibited E-Z-E photoisomerization, however, these materials tend to remain in the Z configuration whenever photoisomerized even to a small extent. Nevertheless, the relaxation process to E configuration was slightly accelerated when the alkyl substituents were branched, which can be attributed to the steric effect caused by the alkyl chains when in the Z-configuration.